THE EFFECT OF NON-CASH TRANSACTIONS ON COMMERCIAL BANK CREDIT CHANNELING AND ITS IMPLICATIONS ON ECONOMIC GROWTH - Salsabilla, Hanum (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study is based on the start of the evolution of payment system that is driven by technology development, which can be seen in recent change of the use of cash transaction to be non-cash transaction in Indonesia. The purpose of this paper is to test the impact non-cash transaction on credit channeling and how it stimulates the economy. This study represents the transaction number of credit card, debit card, e-money, clearing, and Real Time Gross Settlement. By using multiple linear regression, the impact of these representatives on commercial bank lending are tested. The result confirms that only credit card, debit card, and Real Time Gross Settlement affect the credit channeled. However, all transactions affect altogether on credit channeling. Previous studies examine the direct source of fund for banks, which will be released in the form of lending for the society, but ignores the payment system evolution that changes the source’s behavior. This paper contributes to the literature by examining and representing the impact of technology development on payment system, society’s behavior, government’s response, and shows their effects on bank’s intermediary function in the form of credit, which further stimulates the economy.Keywords: credit channeling, non-cas transaction, money multipiler, payment system evolution